(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Nworie River is a popular stream that flows approximately 5km across Owerri metropolitan area in Imo State, the south-eastern part of Nigeria. Many households and industries near Nworie River channel their waste pipes into Nworie River. Such nefarious activities have poisoned the water, thus, the water is highly acidic. One hardly sees fishes in the stream. Despite the dirty nature of the river, many inhabitants of the area still use it for various domestic purposes. Because of the epileptic nature of the public water supply in Owerri and environs, Nworie River serves as a source of drinking water for the plebeians dwelling around the river. An open ended interview and a structured questionnaire were used to collect data from 100 inhabitants of the area was analyzed using simple percentage. It was revealed that the people of the area really make use of water Nworie River for cooking and drinking. It was also revealed that drinking with water from Nworie River has the potential of causing, health problems, unhappiness and psychological breakdown to its users.